Person Identifiers in MARC 21 Records in a Semantic Environment - Serra, Liliana Giusti [UNESP]; Schneider, Jodi A.; Segundo, José Eduardo Santarém [UNESP] (Taylor & Francis, 2020)
This article discusses how libraries can include person identifiers in the MARC format. It suggests using URIs in fields and subfields to help transition the data to an RDF model, and to help prepare the catalog for a Linked Data. It analyzes the selection of URIs and Real-World Objects, and the use of tag 024 to describe person identifiers in authority records. When a creator or collaborator is identified in a work, the identifiers are transferred from authority to the bibliographic record. The article concludes that URI-based descriptions can provide a better experience for users, offering other methods of discovery.
Keywords: cataloging; identity management; linked data; MARC 21; metadata; Person identifiers; RDF model